Molecular Docking, Synthesis and anti-HIV-1 Protease Activity of Novel Chalcones - Turkovic, Nemanja; Ivkovic, Branka; Kotur-Stevuljevic, Jelena; Tasic, Milica; Marković, Bojan; Vujic, Zorica (Current Pharmaceutical Design, 2020)
Background: Since the beginning of the HIV/AIDS epidemic, 75 million people have been infected with the HIV and about 32 million people have died of AIDS. Investigation of the molecular mechanisms critical to the HIV replication cycle led to the identification of potential drug targets for AIDS therapy. One of the most important discoveries is HIV-1 protease, an enzyme that plays an essential role in the replication cycle of HIV. Objective: The aim of the present study is to synthesize and investigate anti-HIV-1 protease activity of some chalcone derivatives with the hope of discovering new lead structure devoid drug resistance. Methods: 20 structurally similar chalcone derivatives were synthesized and their physico-chemical characterization was performed. Binding of chalcones to HIV-1 protease was investigated by fluorimetric assay. Molecular docking studies were conducted to understand the interactions. Results: The obtained results revealed that all compounds showed anti-HIV-1 protease activity. Compound C1 showed the highest inhibitory activity with an IC50 value of 0.001 μM, which is comparable with commercial product Darunavir. Conclusion: It is difficult to provide general principles of inhibitor design. Structural properties of the compounds are not the only consideration; ease of chemical synthesis, low molecular weight, bioavailability, and stability are also of crucial importance. Compared to commercial products the main advantage of compound C1 is the ease of chemical synthesis and low molecular weight. Furthermore, compound C1 has a structure that is different to peptidomimetics, which could contribute to its stability and bioavailability.
Keywords: chalcones